Structural geometry and controlling factors for a rock slope failure area at Hompen/Váráš, Signaldalen, Troms, North Norway - Hannus, Maria (Universitetet i Tromsø, 2012)
Abstract This thesis uses a multidisciplinary approach to investigate factors affecting the origin and evolution of a rock slope failure (RSF) at Hompen (Varas) in Troms, Northern Norway. These factors include internal existing structures in the bedrock, external factors such as glacial unloading, and changes in fluid pressure affecting the RSF. The study combines bedrock geology, structural geology, geomorphology, and satellite data and dGPS measurements to analyze and classify the area. Detailed field work, analyses of field data, DEM models and aerial photos are employed to interpret the RSF. The area has been divided into two domains based on observed structures. Domain I show classical RSF morpho-structures: a major scarp striking NW-SE, lateral scarps striking NE-SW, counter scarps and transfer structures. Domain II is stable but show clear pre-rock slope failure structures, e.g. major tensile fractures, which potentially may enlarge the main RSF area. Among interpreted movement mechanism, creep occurs at present towards SSW (7-10 mm/year) as indicated by dGPS data. There is also clear evidence of toppling as a failure mechanism, shown by the major graben area filled with toppled rock material. The detachment surface is assumed to be of ramp-flat geometry with several sliding planes, affected by fractures working their way down to a basal detachment. The initiation of the RSF is likely linked to pre-existing fracture systems inherited from Mesozoic-Cenozoic tectonic regimes, release of stress regimes in the bedrock after de-glaciation. Other factors such as permafrost melting and water drainage may have caused changes in the pore fluid pressure in the area. Today the Hompen RSF can be classified as a complex RSF field and classifies under the deep seated gravitational slope deformations (DSGSD).